Secure opportunistic access control in D2D-enabled cellular network - Yajun CHEN; Xinsheng JI; Kaizhi HUANG; Jing YANG; Ming YI (Tongxin xuebao)
The mutual interference between cellular links and D2D links can bring the secrecy gain to cellular users in D2D-enable cellular networks.To make full use of them,a cooperative secrecy transmission scheme was proposed based on wireless channels.The channel direction information and gains depict the interference from D2D links to cellular links and other D2D links in the proposed scheme.Firstly,only the D2D users which meet the limited interference conditions were accessed to cellular networks to ensure their reliable communications.It was assumed that legitimate users and eavesdroppers were independent two-dimensional homogeneous Poisson point processes (PPP) distribution.Then the security outage probability (SOP) was derived for cellular users and the connection outage probability (COP) for D2D users,and the impacts of interference thresholds were discussed on their performances.Next,an optimization model was given to minimize D2D users’ COP while ensuring the secrecy performance requirements of cellular users,thus achieving the optimal performance.Finally,simulation results verify the validity of the proposed scheme.